Airway management during in-hospital cardiac arrest in adults: UK national survey and interview study with anaesthetic and intensive care trainees. (August 2021) - Goodwin, Laura; Samuel, Katie; Schofield, Behnaz; Voss, Sarah; Brett, Stephen J; Couper, Keith; Gould, Doug; Harrison, David; Lall, Ranjit; Nolan, Jerry P; Perkins, Gavin D; Soar, Jasmeet; et al.
Background: The optimal airway management strategy for in-hospital cardiac arrest is unknown. Methods: An online survey and telephone interviews with anaesthetic and intensive care trainee doctors identified by the United Kingdom Research and Audit Federation of Trainees. Questions explored in-hospital cardiac arrest frequency, grade and specialty of those attending, proportion of patients receiving advanced airway management, airway strategies immediately available, and views on a randomised trial of airway management strategies during in-hospital cardiac arrest. Results: Completed surveys were received from 128 hospital sites (76% response rate). Adult in-hospital cardiac arrests were attended by anaesthesia staff at 40 sites (31%), intensive care staff at 37 sites (29%) and a combination of specialties at 51 sites (40%). The majority (123/128, 96%) of respondents reported immediate access to both tracheal intubation and supraglottic airways. A bag-mask technique was used 'very frequently' or 'frequently' during in-hospital cardiac arrest by 111/128 (87%) of respondents, followed by supraglottic airways (101/128, 79%) and tracheal intubation (69/128, 54%). The majority (60/100, 60%) of respondents estimated that ≤30% of in-hospital cardiac arrest patients undergo tracheal intubation, while 34 (34%) estimated this to be between 31% and 70%. Most respondents (102/128, 80%) would be 'likely' or 'very likely' to recruit future patients to a trial of alternative airway management strategies during in-hospital cardiac arrest. Interview data identified several barriers and facilitators to conducting research on airway management in in-hospital cardiac arrest. Conclusions: There is variation in airway management strategies for adult in-hospital cardiac arrest across the UK. Most respondents would be willing to take part in a randomised trial of airway management during in-hospital cardiac arrest.